Re-presenting the past - Bonde, Sheila (Joukowsky Institute publication, 2013)
The archaeological past exists for us through intermediaries. Some are written works, descriptions, narratives and field notes, while others are visual: the drawings, paintings, photographs, powerpoints or computer visualizations that allow us to re-present past forms of human existence. This volume brings together nine papers, six of which were presented at a symposium hosted at Brown University. Two papers explore the classical past and medieval visualizations. Three treat the Maya, and one considers the imaging by eighteenth-century antiquarians of British history; yet another ranges broadly in its historical considerations. Several consider the trajectory over time of visualization and self-imaging. Others engage with issues of recording by looking, for example, at the ways in which nineteenth-century excavation photographs can aid in the reconstruction of an inscription or by evaluating the process of mapping a site with ArcGIS and computer animation software. All essays raise key questions about the function of re-presentations of the past in current archaeological practice